Foundations for Aboriginal Adult Literacy - Eileen M. Antone; Peter Gamlin (Adult Education Research Conference, 2004)
Aboriginal adult literacy must be firmly rooted in the traditions of Aboriginal people, which continue to be applicable today in the twenty first century. Aboriginal literacy facilitates the development of self determination, affirmation, achievement and sense of purpose. In terms of foundational Aboriginal literacy we found that we must first understand the meaning of Aboriginal literacy in its broadest sense. Consequently Aboriginal literacy programs must reflect a broad approach that recognizes the unique ways that Aboriginal people represent their experience and knowledge. The medicine wheel is an organizing tool used to conceptualize, reframe and revitalize Aboriginal adult education.